2010
DOI: 10.1002/hep.23639
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver and fibrosis in glycine N-methyltransferase knockout mice is prevented by nicotinamide

Abstract: Deletion of glycine N-methyltransferase (GNMT), the main gene involved in liver S-adenosylmethionine (SAM) catabolism, leads to the hepatic accumulation of this molecule and the development of fatty liver and fibrosis in mice. To demonstrate that the excess of hepatic SAM is the main agent contributing to liver disease in GNMT knockout (KO) mice, we treated 1.5-month-old GNMT-KO mice for 6 weeks with nicotinamide (NAM), a substrate of the enzyme NAM N-methyltransferase. NAM administration markedly reduced hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 38 publications
3
84
0
1
Order By: Relevance
“…Moreover, apoptosis increases and genes involved in inflammation are induced. At 9 months, the GNMT 2/2 mouse also spontaneously develops multifocal HCC (Martinez-Chantar et al, 2008;Varela-Rey et al, 2010). SHP was found repressed in the liver of GNMT 2/2 mice, particularly 9-month-old deficient mice that exhibit more manifest liver disease (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, apoptosis increases and genes involved in inflammation are induced. At 9 months, the GNMT 2/2 mouse also spontaneously develops multifocal HCC (Martinez-Chantar et al, 2008;Varela-Rey et al, 2010). SHP was found repressed in the liver of GNMT 2/2 mice, particularly 9-month-old deficient mice that exhibit more manifest liver disease (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…One major difference among these NAFLD models is that the livers of GNMT 2/2 and MCD diet mice show early symptoms of severe disease with fibrosis and even HCC in GNMT 2/2 (Anstee and Goldin, 2006;Martinez-Chantar et al, 2008;Varela-Rey et al, 2010;Itagaki et al, 2013), whereas MAT1A 2/2 express a less severe phenotype with delayed onset and no fibrosis or HCC (Lu et al, 2001;Martinez-Chantar et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several putative metabolites identified in Gnmt -/-mice serum closely resemble those of NAFLD patients (31). Varela-Rey et al (32) also showed that nicotinamide administration normalized hepatic Sadenosylmethionine (SAM) and fatty acid metabolism, as well as prevented fatty liver development in Gnmt -/-mice. However, the molecular mechanisms of GNMT deficiency-induced hepatic cholesterol accumulation remain unclear.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, accumulation of triglyceride and free fatty acids was also observed in Gnmt -/-mice liver (data not shown), indicating that loss of GNMT widely affects lipids metabolism. Because GNMT is abundantly expressed in normal liver cytosol, we cannot rule out other modulations such as GNMT loss-induced high SAM level (32), or other possibilities on GNMT and other lipid metabolism-related protein interactions.…”
mentioning
confidence: 99%